Volumetric properties for the ternary system (CaCl2-SrCl2-H2O) and binary sub-systems at temperatures from 278.15 K to 323.15 K. (March 2022) - Ge, Haiwen; Wang, Min
Highlights: Volumetric properties of the mixture electrolytes in calc-strontium separation system were studied. Densities for for the ternary system (CaCl2 -SrCl2 -H2 O) and binary sub-systems were determined. Single-salt parameters and mixing ion-interaction parameters were obtained. Temperature-dependence equations for single-salt and mixing parameters were obtained. Abstract: Densities the ternary system (CaCl2 -SrCl2 -H2 O) and its binary sub-systems (CaCl2 -H2 O and SrCl2 -H2 O) were elaborately measured with an Anton Paar Digital vibrating-tube densimeter at temperature intervals of 5 K from 278.15 K to 323.15 K. The coefficient of thermal expansion ( α ) and apparent mole volume ( φ V ) for the binary systems were obtained based on the experimental density results. Apparent mole volumes of CaCl2 and SrCl2 varied smoothly with solute molality and could be fitted using an extended RRM equation. Based on the PK method, the density for the ternary system was predicted by the density of the two binary sub-systems, and there is a good consistency between the results of predicted and experimental. On the basis of volumetric property data for the binary and ternary systems, the Pitzer single-salt parameters ( β MX ( 0 ) V, β MX ( 1 ) V and C MX V, MX = CaCl2 and SrCl2 ) and mixing ion-interaction parameters θ Ca, Sr V, ψ Ca, Sr, Cl V ) were parameterized according to Pitzer ion-interaction theory of single salt electrolyte and mixture electrolytes, respectively. Volumetric property was analysed using the Pitzer model and the predicted values were comparable with experimental values. The simulation results indicate that the Pitzer model parameters can reliably represent the properties of the systems. The temperature-dependence equations and the temperature correlation coefficients for those parameters were also obtained. The volume properties of three systems can be quantitatively obtained according to the electrolyte parameterization model within the experimental temperature range.